Local anesthesia injection technique for aesthetic removal of dermal nevi. (22nd June 2016) - Zaiac, Martin; Shah, Vidhi V; Mlacker, Stephanie; Bray, Fleta N; Alsaidan, Mohammed
Summary: Dermatologists should be aware of the surgical techniques that reduce the level of skin distortion following biopsy procedures. (1) a dilution of lidocaine with bacteriostatic 0.9% sodium chloride and (2) injection of the solution directly into the nevus. The nevus balloons in size and shape and becomes tenser resulting in a change in the skin level permitting for easy shave. Good injection technique of anesthesia may represent a simple, but important means to improve postoperative cosmetic outcomes.